2012
DOI: 10.1111/j.1654-1103.2012.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Does complementarity in leaf phenology and inclination promote co‐existence in a species‐rich meadow? Evidence from functional groups

Abstract: Question Could tests of proportionality for functionally defined guilds provide a rapid means of revealing potential mechanisms of co‐existence in species‐rich meadow communities? Study site A species‐rich meadow in Slovenia. Methods Species presence/absence was recorded in 830 contiguous 0.2 m × 0.2 m quadrats arranged in a rectangular transect. Evidence for guild proportionality was assessed for guilds defined by (1) taxonomy, (2) growth form and (3) functional group defined by leaf inclination or leaf pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…; Mason et al. ). RaoQ, on the other hand, is related both to functional richness and divergence, and this may have created some noise in our results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Mason et al. ). RaoQ, on the other hand, is related both to functional richness and divergence, and this may have created some noise in our results.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, functional divergence measures how far highly abundant species are from the centre of the functional space, and should increase when niche complementarity enhances species' relative abundances (Mouchet et al 2010;Mason et al 2013). We calculated two indices of functional divergence: F Div (Vill eger et al 2008) and RaoQ (Botta-Dukat 2005), although the latter was shown to also be related to functional richness (Mouchet et al 2010).…”
Section: Selection and Calculation Of Diversity Indicesmentioning
confidence: 99%
“…Phenological differences between species may be an important mechanism of niche differentiation, avoiding exclusion between competing species (Chuine ; Mason et al. ). Furthermore, phenological patterns in plant growth influence ecosystem processes through alterations of nutrient uptake, decomposition, and primary production (Polgar & Primack ).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest species richness in karst landscapes is found in dry karst grasslands (Batalha, Pipenbaher, Bakan, Kaligarič, & Škornik, ; Mason, Pipenbaher, Škornik, & Kaligarič, ), and this has also been determined for the Kras Plateau. The plateau is characterized by numerous dolines (over 14,000; mean land surface of 1,800 m 2 ), which experience environmental conditions different to those of the surrounding flat areas.…”
Section: Discussionmentioning
confidence: 84%